The Effect of Playing Exercises on the Concentration of cortisol Hormone for Futsal Players - Hamad. K .Y; Abdullah. M .T; Alaa. J. M (Indonesian Journal Publisher, 2024)
The importance of research in employing playing exercises in building a training program based on the fact that integrated performance in this game depends on the interaction and entry of cortisol hormone and what are the functional changes to bring the training program (used in the research) to the safe side. The researcher uses the experimental method by designing two equal groups, control and experimental, to make it suitable. The research problem is that the experimental method is “an intentional and controlled change to the specific conditions of the phenomenon and to observe the results of the change in the phenomenon that is the subject of the study. The research community is determined in an intentional way, represented by the Kirkuk Educational Futsal Team players for the academic year (2023-2024). The number of players is (20) and the research sample was chosen intentionally and consisted of (18) players representing (80%) of the research community. Thus, they were divided into two experimental and control groups by drawing a lottery with (8) players for each group, after the researcher excluded (4) players, namely goalkeepers and injured players. To achieve the objectives of the study, the researcher assumed the significance of the differences in the results of the pre- and post-tests for the two research groups (control and experimental) in the concentration of the cortisol hormone for futsal players. The significance of the differences in the results of the post-test for the two research groups (control and experimental) in the concentration of the cortisol hormone for futsal players. The researcher reaches a set of conclusions, the most important of which are: The use of playing exercises carried out by the experimental group significantly outperformed the control group in the concentration of the cortisol hormone, as we notice its return to its normal level after 24 minutes of rest during the evening period. So, this indicates that the training program prepared by the researcher is in accordance with the correct scientific foundations.